The reality of e-learning in the distance learning program in light of the emerging Corona pandemic "Covid-19" from the viewpoint of students in Jordan between theory and practice - Aljarrah, Faisal Saleh Freah (Journal of Educational and Psychological Sciences, 2020)
The aim of this research is to identify the reality of e-learning in the distance learning program in light of the emerging Corona pandemic "Covid 19" from the viewpoint of students in Jordan between theory and practice. To achieve the goal of the study, the researcher prepared an electronic questionnaire that included (20) items distributed to the research sample electronically. It was confirmed its sincerity and consistency, and it was applied to a random sample from the study community consisting of (1200) students, and the descriptive analytical method was used. An analytical descriptive approach was used, The study concluded the following results: The importance of using e-learning in distance learning programs, the extent of using e-learning in distance learning programs. There are difficulties preventing the use of e-learning in distance learning programs. There were no statistically significant differences at (05.0 ≤ α) between the responses of the sample members of students about the reality of e-learning in distance learning programs due to gender variables. In light of these results, the study recommended encouraging and educating students to take advantage of the e-learning technology in order to facilitate and improve educational learning practice under the current circumstances. And strengthening the positive trend towards employing e-learning technology and benefiting from Arab and international experiences and expertise in the field of employing e-learning technology in distance learning programs.